Analisis Kesulitan Guru dalam Menerapkan Pendekatan Matematika Realistik di Kelas III D MIN 2 Kota Mataram - Ismi Sabina; Muhammad Rifaldi; Muhammad Rifki Hermawan; Djuita Hidayati (Pusat Riset dan Inovasi Nasional, 2025)
This research was conducted to determine the difficulties experienced by teachers when teaching using a realistic mathematics approach or the Realistic Mathematics Education (RME) approach. This research uses a qualitative method with a descriptive qualitative approach. The data collection techniques used were interviews and observation. This research was carried out by us students at the Mataram State Islamic University. The research was located at MIN 2 Mataram City, specifically on class III D teachers. Researchers also analyzed the data using qualitative data analysis, based on the results obtained from interviews and observations which were then described. The results of interviews and observations show that the difficulties experienced by teachers when teaching using a realistic mathematics approach are the large number of students, classroom conditions, time and limited learning media.